PSXVII-28 Analysis of genetic diversity using microsatellite DNA for genetic structure. (7th December 2018) - Lang, X; Wang, C; Wu, J; Casper, D
Abstract: Approximately, 700 to 800 purebred Minxian Black fur sheep famous for their black fur, exist in a total population of approximately 4, 000. The objective was to determine the remaining genetic diversity for protecting the gene resource by increasing numbers. Random blood samples containing EDTA were collected from representative groups resulting in 60 fresh blood samples (10 males and 50 females). Fifteen microsatellite loci were chosen from the literature based on similar proportion of marker forms; loci evenly distributed through the autosomes and preferably unlinked; and loci exhibit Mendelian inheritance and at least four alleles. These 15 microsatellite loci were recommended by FAO and ISAG and verified with GENEBANK. The frequency and fragment range of alleles were calculated by Excel Microsatellite Toolkit. polymorphism information contents (PIC), number of effective alleles (Ne) and heterozygosity (He) were analyzed by Dispan software. The allele differences electrophoresed on 2% agarose gel were almost not detected due to little change in base numbers and agarose gel inability to distinguish. The individual genotype was judged by the size of the amplified allele fragments and one band was homozygote and two bands were heterozygote. There were 160 alleles at 15 microsatellite loci and the mean was 10.67. The highest 15 alleles were at the loci FCM128 and BM6506, while the 6 lowest alleles were at loci OarAE129. The fragment length was 101 to 147 and 184 to 234, while the allele frequency was 0.0484 to 0.1613 for loci FCM128 and BM6506, respectively, while the fragment length was 145 to 175 with an allele frequency of 0.0323 to 0.3548 for loci OarAE129. The PIC at the FCB128 loci was highest at 0.9108, while, the BM8125 loci was lowest at 0.7788 with a mean PCI of 0.8615, so, all loci were polymorphism. Minxian black fur sheep possess abundant genetic diversity.